Towards a community-based ethical contract. (17th November 2022) - Beck, Dave; Purcell, Rod
Abstract: This article argues that to be effective, community development ethics need to be embedded in community development practice. In the professional experience of the authors, ethics are often said by community development practitioners to be important in theory but may seem abstract or have little impact on day-to-day work. We therefore argue that to bridge that gap between theory and practice the establishment of an ethical contract between community workers and the groups that they work with should be seen as an indispensable element of good practice. We suggest that for an ethical contract to be effective it should be established by workers and community groups working in inclusive and participative ways. This will increase the degree to which ethical practice is understood and owned by all participants and opens up opportunities for practice to be accountable to everyone involved in the community development process and not just professional workers. Drawing on human rights literature and insights from popular education, the article highlights the ways in which using a static ethics framework (such as a statement of ethical principles or code of ethics) may reinforce existing power imbalances and inadvertently disempower communities. It explores how establishing a dynamic ethical contract between practitioners and the groups they work with offers greater potential for embedding ethical practice in community development work.